Experi?ncias formativas e curriculares: implica??es na pr?tica pedag?gica de professoras licenciadas em pedagogia - Santos, Karine Cerqueira dos (2024)
This study is inserted in the debates on training and curricular experiences and aims to understand the implications of these experiences in the pedagogical practice of teachers graduated in Pedagogy from the State University of Feira de Santana/UEFS, since we conceive training as a fundamental aspect for the educational work in Basic Education. The text's main theoretical basis is the studies by Macedo (2010; 2011), Josso (2004), N?voa (1992) and Franco (2016). As methodological paths, the (auto)biographical approach was adopted in this research, taking the training narratives as a training device and the narrative interview as a research device, since the production of narratives provided by (auto)biography contributes to greater awareness of themselves and their existentiality in the world, leading narrators to think about their experiences and how they are remade each time they are narrated. The study had three teachers as collaborators who, when narrating their stories, revealed how the experiences they had at university have implications for their pedagogical practice. It was concluded that the formative experiences experienced within the teacher training course in the Degree in Pedagogy have implications for the teachers' pedagogical practice, mainly in the mobilization of the necessary knowledge and identification for teaching work.